INTEGRATION MECHANISMS OF IMPROVEMENT OF HUMAN RESOURCES MANAGEMENT - Vera A. Akimenko (Статистика и экономика)
In the current economic conditions, the efficiency of business processes of an organization is determined by the quality of the staff. Therefore, actual is the creation and application of new approaches to the management of human re-sources. The article presents a comparative analysis of management practices and their impact on the effectiveness of personnel management, the mechanism of their integration to improve the efficiency of the process.